Magnitude of workplace violence and its associated factors against nurses working in public hospitals of Western Ethiopia: a cross-sectional study - Sidise Temesgen; Lammi Atomsa; Dawit Teklehymanot; Takele Tiki; Seifadin Ahmed (BMC, 2024)
Abstract Background Workplace violence (WPV) is a situation in which employees are harassed, intimidated, or assaulted at work or while commuting to and from work. Even though WPV can result in physical and psychological suffering, little evidence is available in Ethiopia. Hence, this study aimed to assess magnitude of workplace violence and its associated factors against nurses working in public hospitals of Western Ethiopia. Methods An institution based cross-sectional study was carried out among nurses working in five public hospitals found in east Wollega from September 15 to October 1, 2022. A simple random sampling technique was used to select 396 study participants. Self-administered adapted questionnaire and semi structured questionnaires were used to collect data. Data was coded and entered Epi data 3.1 and exported to SPSS version 20 analysis. Bi-variable and multivariable logistic regressions were done. Level of association was determined using adjusted odds ratio at 95% confidence interval and p-values of < 0.05. Results The prevalence of Workplace violence in the last 12 months was 42.8%. Age group 25-29 years [AOR:3.93, 95% CI = 1.2, 13.3) and 30-34 years [AOR:4.01, 95%CI = 1.4, 11.8], Married nurses [AOR:0.4, 95%CI = 0.2, 0.92], work experience = < 5 years [AOR:2.21, 95%CI = 1.27, 3.82] working between 6:30- 7:30 PM o'clock [AOR:3.49,95%CI = 1.4,8.62], availability of reporting system [AOR:2.58, 95%CI = 1.04, 6.4], Encouragement to report violence[AOR:3.98, 95%CI = 2.05, 7.72], substance use [AOR:3.56, 95%CI = 1.49, 8.46] and nurses ever stressed by job [AOR:3.66, 95%CI = 1.8, 7.34] were significantly associated with workplace violence. Conclusion and recommendation In the current study Workplace violence among nurses was high. Therefore, an intervention like developing reporting system, encouragement to report the violence and training that focuses on prevention and controlling of violence is recommended.